Technology-Assisted Review and business resolution for the benefit of the masses - CONCEIÇÃO, Ana Filipa (Revista Jurídica Portucalense, 2022)
Artificial intelligence, namely Technology Assisted Review instruments, are the future helper of legal professionals, including insolvency practitioners. This paper will concern the possibilities brought by the introduction of TAR in insolvency procedures. Avoidance actions allow the debtors to subtract assets, not only at a national, but on an European level, leaving creditors unpaid. Since insolvency practitioners face practical problems to recuperate those assets, we will analyze the Portuguese legislation, the difficulties, and the possibilities brought by TAR.